2018
DOI: 10.1002/nla.2220
|View full text |Cite
|
Sign up to set email alerts
|

A parallel time integrator for solving the linearized shallow water equations on the rotating sphere

Abstract: Summary With the stagnation of processor core performance, further reductions in the time to solution for geophysical fluid problems are becoming increasingly difficult with standard time integrators. Parallel‐in‐time exposes and exploits additional parallelism in the time dimension, which is inherently sequential in traditional methods. The rational approximation of exponential integrators (REXI) method allows taking arbitrarily long time steps based on a sum over a number of decoupled complex PDEs that can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…Exponential integrators allow for solving the linearized SWE (L g ) on the rotating sphere (including L c ) with very high accuracy [9,38]. Furthermore, exponential integrators have been shown to support time steps as long as 1.5 days [38].…”
Section: Exponential Time Integration For Swementioning
confidence: 99%
See 2 more Smart Citations
“…Exponential integrators allow for solving the linearized SWE (L g ) on the rotating sphere (including L c ) with very high accuracy [9,38]. Furthermore, exponential integrators have been shown to support time steps as long as 1.5 days [38].…”
Section: Exponential Time Integration For Swementioning
confidence: 99%
“…Exponential integrators allow for solving the linearized SWE (L g ) on the rotating sphere (including L c ) with very high accuracy [9,38]. Furthermore, exponential integrators have been shown to support time steps as long as 1.5 days [38]. It has also been shown that SH provides an ideal basis for REXI to time integrate the linear parts of the SWE [9], even on the rotating sphere [38].…”
Section: Exponential Time Integration For Swementioning
confidence: 99%
See 1 more Smart Citation
“…Krylov solvers, such as those presented in [28], are used in [15] and [25] for the matrix exponentiation of a dynamic linearization of the shallow water system. Furthermore, [48] adopts a rational approximation based on [27] for the rotating SWE on the plane, which is also used for the sphere in [47,49] with a global spectral spherical harmonics representation. This rational approximation approach calculates the matrix exponentials with a very high degree of parallelism, so the additional computational costs of the calculating such exponential may be absorbed by extra compute nodes to still reduce the time-to-solution.…”
Section: Rotating Shallowmentioning
confidence: 99%
“…Small scale horizontal gravity waves play an important role in the large structure of the middle atmosphere, particularly for climate simulations [38]. Exponential integrators provide a way to obtain large time-steps without affecting these small-scale waves, preserving superior linear dispersion properties (see [47,14]).…”
mentioning
confidence: 99%